PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN WISATAWAN NUSANTARA KE CURUG LEUWI HEJO, BOGOR PADA ERA NEW NORMAL - Pangaribuan, Evitauli; Suwena, I Ketut; Sasrawan Mananda, IGPB. (Jurnal IPTA (Industri Perjalanan Wisata), 2021)
Curug Leuwi Hejo is taken from the local Sundanese language which is Curug means waterfall, Leuwi means pond, while Hejo means green. The purpose of this study was to determine the effect of service quality on the satisfaction of domestic tourists visiting Curug Leuwi Hejo, Bogor Regency in the new normal era. The sampling technique used purposive sampling with 100 respondents. The data collection techniques used by observation, interviews, questionnaires, documentation, literature studies, and netnography. The data analysis technique used is mixed methods including qualitative and quantitative descriptive analysis. The results of the research using the t test showed that partially the variables of tangible and empathy have a significant effect on the satisfaction of domestic tourists who visit Curug Leuwi Hejo, Bogor Regency in the new normal era. Meanwhile, the variable reliability, responsiveness, and assurance does not have a significant effect on the satisfaction of domestic tourists visiting Curug Leuwi Hejo, Bogor Regency in the new normal era. Based on the results of the F test showed that simultaneously service quality has a significant and positive effect on the satisfaction of domestic tourists visiting Curug Leuwi Hejo Bogor Regency in the new normal era with a coefficient of determination of 51%.